2010
DOI: 10.1136/fg.2009.000240
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in nutrition support: a view from the coalface

Abstract: Artificial nutrition and hydration continue to stimulate debate among physicians and in the wider world. This review aims to give those involved in providing nutrition support the necessary tools to be confident in making decisions in individual cases. It examines basic ethical principles and suggests a structured approach to ensure all the relevant factors are considered in making decisions. The current legal context and in particular the provisions of the Mental Capacity Act 2005 relating to nutrition suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Professionals have a basic duty to prolong life, serve the patients best interest and balance the ethical principles of justice and beneficence. Care should be fair and equitable for patients in a similar position being treated in a similar manner and a second opinion should be sought when making complex decisions 11…”
Section: Discussionmentioning
confidence: 99%
“…Professionals have a basic duty to prolong life, serve the patients best interest and balance the ethical principles of justice and beneficence. Care should be fair and equitable for patients in a similar position being treated in a similar manner and a second opinion should be sought when making complex decisions 11…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, the following question may arise: why is the belief of artificial nutrition as a viable way to treat patients with dementia so accepted and widely spread? Scientific research has concluded that a patient with advanced dementia does not show benefits from improving their nutritional status 4 , as Nicola Simmonds (Simmonds, 2010), suggests in the article "Ethical issues in nutrition support: a view from the coalface". Moreover, there is another equally important question: why do families insist on artificial nutrition as a feasible treatment for these patients?…”
Section: The View On Food Implications For the Use Of Feeding Tubesmentioning
confidence: 99%
“…This is due mainly to the risk of procedure-related complications and, more rarely, to cases where the proposed intervention may be of no benefit to the patient and consequently deemed “futile” [1, 2]. Since endoscopy is traditionally considered a “minimally invasive” procedure, adopted when invasive surgery is not feasible, ethical problems are relatively rare.…”
mentioning
confidence: 99%